The Distribution of Open Clusters in the Galaxy - Monteiro, Hektor; Barros, Douglas A.; Dias, Wilton S.; Lépine, Jacques R. D. (Frontiers in Astronomy and Space Sciences, 2021)
In this work we explore the new catalog of galactic open clusters that became available recently, containing 1750 clusters that have been re-analysed using the Gaia DR2 catalog to determine the stellar memberships. We used the young open clusters as tracers of spiral arms and determined the spiral pattern rotation speed of the Galaxy and the corotation radius, the strongest Galactic resonance. The sample of open clusters used here increases the last one from Dias et al. (2019) used in the previous determination of the pattern speed by dozens objects. In addition, the distances and ages values are better determined, using improvements to isochrone fitting and including an updated extinction polynomial for the Gaia DR2 photometric band-passes, and the Galactic abundance gradient as a prior for metallicity. In addition to the better age determinations, the catalog contains better positions in the Galactic plane and better proper motions. This allow us to discuss not only the present space distribution of the clusters, but also the space distribution of the clusters's birthplaces, obtained by integration of the orbits for a time equal to their age. The value of the rotation velocity of the arms ($28.5 ± 1.0$ km\,s$^{-1}$\,kpc$^{-1}$) implies that the corotation radius ($R_c$) is close to the solar Galactic orbit ($R_c/R_0 = 1.01±0.08$), which is supported by other observational evidence discussed in this text. A simulation is presented, illustrating the motion of the clusters in the reference frame of corotation. We also present general statistics of the catalog of clusters, like spatial distribution, distribution relative to height from the Galactic plane, and distribution of ages and metallicity. An important feature of the space distribution, the corotation gap in the gas distribution and its consequences for the young clusters, is discussed.